Exploring Factors that Influence Social Retail Investors’ Decisions: Evidence from Desjardins Fund - Diouf, Dominique (Journal of business ethics, 2016)
Most studies on the choices, motivations and behavior of investors consist of segmentations focused on socio-demographic characteristics such as age, income, education level, etc. Such approaches seem to simplify, even mutilate, reality by aggregating data about observable variables and considering investors as homogeneous groups. These perspectives are inspired by a scientific approach that consists of separating in order to better understand the observed phenomena. By considering individual as a “homo economicus”, that is to say, a rational and autonomous individual who makes decisions motivated by material gains, these studies fail to recognize all the complexity that shapes human behavior. This paper argues that to understand the behavior and choices of investors in regards to socially responsible investing (SRI), we must consider social investors as complex individuals. In addition, we should take into account influence that the institution may exercise throughout the role of advisors and SRI promotion strategies. Our research builds on a multidimensional approach that explores to what extent demographic, environmental, social and governance (ESG) issues, the trade-offs between financial return and social values, the attitudes and the role of the institution (throughout the role of the advisor and SRI promotion strategies) influence the decisions of individual social investors. Moreover, it adopts a more open approach by exploring the characteristics and behaviors of individual social investors in relation to those of conventional investors. Our research provides evidence from the Desjardins Fund. Qualitative and quantitative data gathered by Desjardins from online surveys are subjected to bivariate and multivariate analyses and are complimented by ten semi-structured interviews with managers, analysts, and advisors who provided further insight into SRI investment behavior and choice. The results show that while demographic characteristics still remain important in understanding the behavior and attitudes of social investors, it is their social values, ESG issues, financial return considerations and the role played by the institution in mediating investment decisions that are significantly associated with SRI portfolios. Our research highlights the complexity surrounding the phenomenon of SRI and has several implications both in terms of theory and practice.